First Report of Immune Mediated Haemolytic AnaemiaAssociated with Haemoparasitic Infections of Canine inAizawl, Mizoram - Lucy, Elone; Rajesh, J B; Konwar, Bedanga; Tolenkhomba, T C; Prasad, Hridayesh; Sarma, Kalyan; Hmar, Lalnuntluangi; Debnath, Ankita (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was carried out to study the occurrence of immune mediated haemolytic anaemia associated with haemoparasitic infections in dogs in and around Aizawl. A systematic study about IMHA from northeast part of India is lacking and there are no studies conducted in northeast India especially in Mizoram. Hence, there is shortage of scientific data. And since IMHA can be triggered by parasites and there are reports about Ehrlichia canis and Babesia gibsoni in dogs from Mizoram. In view of these background and facts, the occurrence of IMHA associated with haemoparasitic infections in dogs in and around Aizawl, Mizoram was studied. These dogs were selected based on the symptoms like icterus, pale mucus membrane, lethargy, anorexia, fever, and other symptoms associated with haemolytic anaemia. The confirmation was done based on blood smear examination, antibody detection test kit, Coomb’s test, haemato-biochemical screening of serum/plasma and urinalysis for the evidence of haemolytic anaemia. Occurrence of immune mediated haemolytic anaemia associated with haemoparasitic infections in dogs in and around Aizawl was 34.29 %. Babesia gibsoni (75%) was the common causative agent for occurrence of immune mediated haemolytic anaemia associated with haemoparasitic infections in dogs in and around Aizawl.